The Archaeological Survey of Sudanese Nubia, 1963-69 The Pharaonic Sites - Edwards, David N. (Archaeopress Publishing, 2020)
Of the Nubian Archaeological Campaigns responding to the construction of the Aswan High Dam, the survey and excavations carried out within Sudanese Nubia represent the most substantial achievement of the larger enterprise. Many components of the larger project of the UNESCO - Sudan Antiquities Service Survey have been published, in addition to the reports of a number of other major projects assigned separate concessions within the region. However, the results of one major element, the Archaeological Survey of Sudanese Nubia (ASSN) between the Second Cataract and the Dal Cataract remain largely unpublished. This volume, focusing on the pharaonic sites, is the first of a series which aims to bring to publication the records of the ASSN. These records represent a major body of data relating to a region largely now lost to flooding. This is also a region of very considerable importance for understanding the archaeology and history of Nubia more generally, not least in relation to the still often poorly understood relationships between Lower Nubia to the north and the surviving areas of Middle and Upper Nubia, to the south. The ASSN project fieldwork was undertaken over six years between 1963 and 1969, investigating c.130km of the river valley between Gemai, at the south end of the Second Cataract, and Dal.